Nanotechnology for Electronics, Photonics, Biosensors, and Emerging Technologies - Jain, F.; Broadbridge, C. C.; Gherasimova, M.; Tang, H.; Connecticut Microelectronics and Optoelectronics Consortium New Haven, Conn) (Selected topics in electronics and systems, 64, 2021)
Keywords: Congresses; Congresses; Biosensors; Congresses; Nanoelectronics; Congresses; Nanophotonics; Congresses; Optoelectronics; Nanotechnology; dept.phy; faculty_collection

Convolutional Neural Network for Binary Classification of Chromophobe Renal Cell Carcinoma and Oncocytoma - Cheng, Andrew; Icaza, Michael; Judd, Nicholas; Smith, Jason; Mukherjee, Sushmita; Jain, Manu; Wu, Binlin (Frontiers in Optics, 2021)
Multiphoton microscopy images of chromophobe renal cell carcinoma and renal oncocytoma were classified using a convolutional neural network inspired by techniques in recent architectures and yielded over 70% accuracy.
Keywords: dept.phy

Global Λ-hyperon polarization in Au+Au collisions at √sNN = 3 GeV - STAR Collaboration (Physical Review C, 2021)
Global hyperon polarization, P¯H, in Au+Au collisions over a large range of collision energy, sNN, was recently measured and successfully reproduced by hydrodynamic and transport models with intense fluid vorticity of the quark-gluon plasma. While naïve extrapolation of data trends suggests a large P¯H as the collision energy is reduced, the behavior of P¯H at small sNN¡7.7 GeV is unknown. Operating the STAR experiment in fixed-target mode, we measured the polarization of Λ hyperons along the direction of global angular momentum in Au+Au collisions at sNN=3 GeV. The observation of substantial polarization of 4.91±0.81(stat.)±0.15(syst.)% in these collisions may require a reexamination of the viscosity of any fluid created in the collision, of the thermalization timescale of rotational modes, and of hadronic mechanisms to produce global polarization. © 2021 American Physical Society.
Keywords: dept.phy; peer-reviewed

Measurement of the sixth-order cumulant of net-proton multiplicity distributions in au+au collisions at s NN =27, 54.4, and 200 GeV at RHIC - STAR Collaboration (Physical Review Letters, 2021)
According to first-principle lattice QCD calculations, the transition from quark-gluon plasma to hadronic matter is a smooth crossover in the region μB≤Tc. In this range the ratio, C6/C2, of net-baryon distributions are predicted to be negative. In this Letter, we report the first measurement of the midrapidity net-proton C6/C2 from 27, 54.4, and 200 GeV Au+Au collisions at the Relativistic Heavy Ion Collider (RHIC). The dependence on collision centrality and kinematic acceptance in (pT, y) are analyzed. While for 27 and 54.4 GeV collisions the C6/C2 values are close to zero within uncertainties, it is observed that for 200 GeV collisions, the C6/C2 ratio becomes progressively negative from peripheral to central collisions. Transport model calculations without critical dynamics predict mostly positive values except for the most central collisions within uncertainties. These observations seem to favor a smooth crossover in the high-energy nuclear collisions at top RHIC energy. © 2021 American Physical Society.
Keywords: Au+Au collisions; Colliding beam accelerators; Cumulants; First principles; Germanium alloys; Germanium compounds; Gold compounds; Hadronic matters; Heavy ions; Lattice QCD calculations; Measurements of; Mid-rapidity; Multiplicity distributions; Quantum theory; Quark-gluon plasma; Uncertainty; dept.phy; peer-reviewed

Understanding reentrance in frustrated magnets: The case of the Er2Sn2 O7 pyrochlore - Yahne, D.R.; Pereira, D.; Jaubert, L.D.C.; Sanjeewa, L.D.; Powell, M.; Kolis, J.W.; Xu, G.; Enjalran, M.; Gingras, M.J.P.; Ross, K.A. (Physical Review Letters, 2021)
Reentrance, the return of a system from an ordered phase to a previously encountered less-ordered one as a controlled parameter is continuously varied, is a recurring theme found in disparate physical systems, yet its microscopic cause is often not investigated thoroughly. Here, through detailed characterization and theoretical modeling, we uncover the microscopic mechanism behind reentrance in the strongly frustrated pyrochlore antiferromagnet Er2Sn2O7. We use single crystal heat capacity measurements to expose that Er2Sn2O7 exhibits multiple instances of reentrance in its magnetic field B vs temperature T phase diagram for magnetic fields along three cubic high symmetry directions. Through classical Monte Carlo simulations, mean field theory, and classical linear spin-wave expansions, we argue that the origins of the multiple occurrences of reentrance observed in Er2Sn2O7 are linked to soft modes. These soft modes arise from phase competition and enhance thermal fluctuations that entropically stabilize a specific ordered phase, resulting in an increased transition temperature for certain field values and thus the reentrant behavior. Our work represents a detailed examination into the mechanisms responsible for reentrance in a frustrated magnet and may serve as a template for the interpretation of reentrant phenomena in other physical systems. © 2021 American Physical Society.
Keywords: Antiferromagnets; Binary alloys; Controlled parameter; Crystal symmetry; Frustrated magnet; Intelligent systems; Magnetic fields; Magnetic-field; Magnetization; Magnets; Mean field theory; Microscopic mechanisms; Monte Carlo methods; Ordered phasis; Physical systems; Pyrochlores; Single crystals; Soft modes; Specific heat; Spin waves; Theoretical modeling; dept.phy

A Comprehensive Astrometric Calibration of HST's WFPC2. I. Distortion Mapping - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Kozhurina-Platais, Vera; Platais, Imants; Anderson, Jay; Horch, Elliott P. (Publications of the Astronomical Society of the Pacific, 2021)
Wide field planetary camera 2 (WFPC2) exposures are already some 20 years older than Gaia epoch observations, or future James Webb Space Telescope observations. As such, they offer an unprecedented time baseline for high-precision proper-motion studies, provided the full astrometric potential of these exposures is reached. We have started such a project with the work presented here being its first step. We explore geometric distortions beyond the well-known ones published in the early 2000 s. This task is accomplished by using the entire database of WFPC2 exposures in filters F555W, F606W and F814W and three standard astrometric catalogs: Gaia EDR3, 47 Tuc and ωCen. The latter two were constructed using Hubble Space Telescope observations made with cameras other than WFPC2. We explore a suite of centering algorithms, and various distortion maps in order to understand and quantify their performance. We find no high-frequency systematics beyond the 34th-row correction, down to a resolution of 10 pixels. Low-frequency systematics starting at a resolution of 50 pixels are present at a level of 30–50 millipix (1.4–2.3 mas) for the PC and 20–30 millipix (2–3 mas) for the WF chips. We characterize these low-frequency systematics by providing correction maps and updated cubic-distortion coefficients for each filter.
Keywords: dept.mat; dept.phy; peer-reviewed

Dissecting the Quadruple Binary Hyad vA 351 Masses for Three M Dwarfs and a White Dwarf* - Benedict, G. Fritz; Franz, Otto G.; Horch, Elliott P.; Prato, L.; Torres, Guillermo; McArthur, Barbara E.; Wasserman, Lawrence H.; Latham, David W.; Stefanik, Robert P.; Latham, Christian; Skiff, Brian A. (The Astronomical Journal, 2021)
We extend results first announced by Franz et al., that identified vA 351 = H346 in the Hyades as a multiple star system containing a white dwarf. With Hubble Space Telescope Fine Guidance Sensor fringe tracking and scanning, and more recent speckle observations, all spanning 20.7 years, we establish a parallax, relative orbit, and mass fraction for two components, with a period, and total mass 2.1 . With ground-based radial velocities from the McDonald Observatory Otto Struve 2.1 m Telescope Sandiford Spectrograph, and Center for Astrophysics Digital Speedometers, spanning 37 years, we find that component B consists of BC, two M dwarf stars orbiting with a very short period ( days), having a mass ratio / = 0.95. We confirm that the total mass of the system can only be reconciled with the distance and component photometry by including a fainter, higher-mass component. The quadruple system consists of three M dwarfs (A, B, C) and one white dwarf (D). We determine individual M dwarf masses = 0.53 ± 0.10 , = 0.43 ± 0.04 , and = 0.41 ± 0.04 . The white dwarf mass, 0.54 ± 0.04 , comes from cooling models, an assumed Hyades age of 670 Myr, and consistency with all previous and derived astrometric, photometric, and radial velocity results. Velocities from Hα and He i emission lines confirm the BC period derived from absorption lines, with similar (He i) and higher (Hα) velocity amplitudes. We ascribe the larger Hα amplitude to emission from a region each component shadows from the other, depending on the line of sight.
Keywords: dept.phy; peer-reviewed

HAT-P-58b – HAT-P-64b: Seven planets transiting bright stars - Bakos, G. Á.; Hartman, Joel D.; Bhatti, Waqas; Csubry, Z.; Penev, Kaloyan; Bieryla, Allyson; Latham, D. W.; Quinn, S. N.; Buchhave, Lars A.; Kovács, Gábor L.; Torres, Guillermo; Noyes, R. W.; et al. (The Astronomical Journal, 2021)
We report the discovery and characterization of seven transiting exoplanets from the HATNet survey. The planets, which are hot Jupiters and Saturns transiting bright Sun-like stars, include: HAT-P-58b (with mass M p = 0.37 M J, radius R p = 1.33 R J, and orbital period P = 4.0138 days), HAT-P-59b (M p = 1.54 M J, R p = 1.12 R J, P = 4.1420 days), HAT-P-60b (M p = 0.57 M J, R p = 1.63 R J, P = 4.7948 days), HAT-P-61b (M p = 1.06 M J, R p = 0.90 R J, P = 1.9023 days), HAT-P-62b (M p = 0.76 M J, R p = 1.07 R J, P = 2.6453 days), HAT-P-63b (M p = 0.61 M J, R p = 1.12 R J, P = 3.3777 days), and HAT-P-64b (M p = 0.58 M J, R p = 1.70 R J, P = 4.0072 days). The typical errors on these quantities are 0.06 M J, 0.03 R J, and 0.2 s, respectively. We also provide accurate stellar parameters for each of the host stars. With V = 9.710 0.050 mag, HAT-P-60 is an especially bright transiting planet host, and an excellent target for additional follow-up observations. With R p = 1.703 0.070 R J, HAT-P-64b is a highly inflated hot Jupiter around a star nearing the end of its main-sequence lifetime, and is among the largest known planets. Five of the seven systems have long-cadence observations by TESS which are included in the analysis. Of particular note is HAT-P-59 (TOI-1826.01) which is within the northern continuous viewing zone of the TESS mission, and HAT-P-60, which is the TESS candidate TOI-1580.01. © 2021. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed

Observations with the differential speckle survey instrument. X. Preliminary orbits of k-dwarf binaries and other stars - Horch, Elliott P.; Broderick, Kyle G.; Casetti-Dinescu, Dana I.; Henry, Todd J.; Fekel, Francis C.; Muterspaugh, Matthew W.; Willmarth, Daryl W.; Winters, Jennifer G.; van Belle, Gerard T.; Clark, Catherine; Everett, Mark E. (The Astronomical Journal, 2021)
This paper details speckle observations of binary stars taken at the Lowell Discovery Telescope, the WIYN telescope, and the Gemini telescopes between 2016 January and 2019 September. The observations taken at Gemini and Lowell were done with the Differential Speckle Survey Instrument (DSSI), and those done at WIYN were taken with the successor instrument to DSSI at that site, the NN-EXPLORE Exoplanet Star and Speckle Imager (NESSI). In total, we present 378 observations of 178 systems, and we show that the uncertainty in the measurement precision for the combined data set is ∼2 mas in separation, ∼1°-2° in position angle depending on the separation, and ∼0.1 mag in magnitude difference. Together with data already in the literature, these new results permit 25 visual orbits and one spectroscopic-visual orbit to be calculated for the first time. In the case of the spectroscopic-visual analysis, which is done on the ternary star HD 173093, we calculate masses with a precision of better than 1% for all three stars in that system. Twenty-one of the visual orbits calculated have a K dwarf as the primary star; we add these to the known orbits of K-dwarf primary stars and discuss the basic orbital properties of these stars at this stage. Although incomplete, the data that exist so far indicate that binaries with K-dwarf primaries tend not to have low-eccentricity orbits at separations of one to a few tens of astronomical units, that is, on solar system scales. © 2021 Institute of Physics Publishing. All rights reserved.
Keywords: dept.phy; peer-reviewed

Global polarization of ξ and ω hyperons in au+au collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2021)
Global polarization of Ξ and ω hyperons has been measured for the first time in Au+Au collisions at sNN=200 GeV. The measurements of the Ξ- and Ξ¯+ hyperon polarization have been performed by two independent methods, via analysis of the angular distribution of the daughter particles in the parity violating weak decay Ξ→Λ+π, as well as by measuring the polarization of the daughter Λ hyperon, polarized via polarization transfer from its parent. The polarization, obtained by combining the results from the two methods and averaged over Ξ- and Ξ¯+, is measured to be ⟨PΞ ©=0.47±0.10(stat)±0.23(syst)% for the collision centrality 20%-80%. The ⟨PΞ. © 2021 American Physical Society. All rights reserved.
Keywords: Angular distribution; Au+Au collisions; Colliding beam accelerators; Global polarizations; Hyperon polarization; Measurements of; Polarization; Polarization transfer; dept.phy; peer-reviewed

Measurement of e+e- momentum and angular distributions from linearly polarized photon collisions - STAR Collaboration (Physical Review Letters, 2021)
The Breit-Wheeler process which produces matter and antimatter from photon collisions is experimentally investigated through the observation of 6085 exclusive electron-positron pairs in ultraperipheral Au+Au collisions at sqrt[s_{NN}]=200 GeV. The measurements reveal a large fourth-order angular modulation of cos4DELTAphi=(16.8+/-2.5)% and smooth invariant mass distribution absent of vector mesons (phi, omega, and rho) at the experimental limit of <=0.2% of the observed yields. The differential cross section as a function of e^{+}e^{-} pair transverse momentum P_{} peaks at low value with sqrt[ ]=38.1+/-0.9 MeV and displays a significant centrality dependence. These features are consistent with QED calculations for the collision of linearly polarized photons quantized from the extremely strong electromagnetic fields generated by the highly charged Au nuclei at ultrarelativistic speed. The experimental results have implications for vacuum birefringence and for mapping the magnetic field which is important for emergent QCD phenomena.
Keywords: Angular distribution; Angular-modulation; Au+Au collisions; Colliding beam accelerators; Differential cross section; Electron-positron pairs; Invariant mass distribution; Linearly polarized; Matter and antimatters; Photons; Transverse momenta; dept.phy; peer-reviewed

Observation of Ds± /D0 enhancement in au+au collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2021)
We report on the first measurement of charm-strange meson Ds± production at midrapidity in Au+Au collisions at sNN=200 GeV from the STAR experiment. The yield ratio between strange (Ds±) and nonstrange (D0) open-charm mesons is presented and compared to model calculations. A significant enhancement, relative to a pythia simulation of p+p collisions, is observed in the Ds±/D0 yield ratio in Au+Au collisions over a large range of collision centralities. Model calculations incorporating abundant strange-quark production in the quark-gluon plasma and coalescence hadronization qualitatively reproduce the data. The transverse-momentum integrated yield ratio of Ds±/D0 at midrapidity is consistent with a prediction from a statistical hadronization model with the parameters constrained by the yields of light and strange hadrons measured at the same collision energy. These results suggest that the coalescence of charm quarks with strange quarks in the quark-gluon plasma plays an important role in Ds±-meson production in heavy-ion collisions. © 2021 authors. Published by the American Physical Society. Funded by SCOAP3.
Keywords: Au+Au collisions; Bosons; Coalescence; Colliding beam accelerators; Collision energies; Collisional plasmas; Germanium compounds; Gold compounds; Hadrons; Heavy ion collision; Heavy ions; Meson production; Model calculations; Quantum theory; Quark production; Quark-gluon plasma; Transverse momenta; dept.phy; peer-reviewed

Nonmonotonic energy dependence of net-proton number fluctuations - STAR Collaboration (Physical Review Letters, 2021)
Nonmonotonic variation with collision energy (sNN) of the moments of the net-baryon number distribution in heavy-ion collisions, related to the correlation length and the susceptibilities of the system, is suggested as a signature for the quantum chromodynamics critical point. We report the first evidence of a nonmonotonic variation in the kurtosis times variance of the net-proton number (proxy for net-baryon number) distribution as a function of sNN with 3.1 σ significance for head-on (central) gold-on-gold (Au+Au) collisions measured solenoidal tracker at Relativistic Heavy Ion Collider. Data in noncentral Au+Au collisions and models of heavy-ion collisions without a critical point show a monotonic variation as a function of sNN. © 2021 American Physical Society.
Keywords: Colliding beam accelerators; Collision energies; Correlation lengths; Gold; Hadrons; Heavy ion collision; Heavy ions; Ion sources; Monotonic variations; Non-monotonic variation; Number fluctuations; Quantum chromodynamics; Quantum theory; Relativistic Heavy Ion Collider; dept.phy; peer-reviewed

Analysis of Stokes shift spectra for distinguishing human prostate cancerous and normal tissues using machine learning methods - Mo, Haiding; Wang, Eric; Tian, Yuke; Pu, Yang; Wu, Binlin; Alfano, Robert R. (SPIE, 2021)
Early detection of prostate cancer is critical for the success of cancer therapy. It is believed that the biochemical changes that cause the optical spectra changes would appear earlier than the histological aberration. The aim of this ex vivo study was to evaluate the ability of Stokes Shift Spectra (S3) to identify human prostate cancerous tissues from the normal. Fifteen (15) pairs of with pathologically confirmed human prostate cancerous and normal tissues underwent Stokes Shift Spectra measurements with selective wavelength interval of 40 nm. The spectra were then analyzed using machine learning (ML) algorithms to classify the two types of tissues. The ML algorithms including principal component analysis (PCA) and nonnegative matrix factorization (NMF) were used for dimension reduction and feature detection. The characteristic component spectra were used to identify the key fluorophores related to carcinogenesis. The results show that these key fluorophores within tissue, e.g., tryptophan, collagen, and NADH, have different relative concentrations between cancerous and normal tissues. A multi-class classification was performed using support vector machines (SVMs). A leave-one-out cross validation was used to evaluate the performance of the classification with the gold standard histopathological results as the ground truth. The results with high sensitivity and specificity indicate that the S3 method is effective for detecting changes of fluorophore composition in human prostate tissues due to the development of cancer. © 2021 SPIE.
Keywords: Amino acids; Diagnosis; Dimension reduction; Diseases; Factorization; Fluorophores; Histology; Learning systems; Leave-one-out cross validations; Machine learning methods; Matrix algebra; Multi-class classification; Nonnegative matrix factorization; Relative concentration; Spectra measurements; Statistical methods; Support vector machine (SVMs); Support vector machines; Tissue; Tissue engineering; Urology; dept.phy

Speckle imaging characterization of radial velocity exoplanet systems - Dalba, Paul A.; Kane, Stephen R.; Howell, Steve B; Horch, Elliott P; Li, Zhexing; Hirsch, Lea A.; Burt, Jennifer; Brandt, Timothy D.; Močnik, Teo; Henry, Gregory W. (Astronomical Journal, 2021)
We conducted speckle imaging observations of 53 stellar systems that were members of long-term radial velocity (RV) monitoring campaigns and exhibited substantial accelerations indicative of planetary or stellar companions in wide orbits. Our observations were made with blue and red filters using the Differential Speckle Survey Instrument at Gemini-South and the NN-Explore Exoplanet Stellar Speckle Imager at the WIYN telescope. The speckle imaging identifies eight luminous companions within 2" of the primary stars. In three of these systems-HD 1388, HD 87359, and HD 104304-the properties of the imaged companion are consistent with the RV measurements, suggesting that these companions may be associated with the primary and the cause of the RV variation. For all 53 stellar systems, we derive differential magnitude limits (i.e., contrast curves) from the imaging. We extend this analysis to include upper limits on companion mass in systems without imaging detections. In 25 systems, we rule out companions with masses greater than 0.2 M⊙, suggesting that the observed RV signals are caused by late-M dwarfs or substellar (potentially planetary) objects. On the other hand, the joint RV and imaging analysis almost entirely rules out planetary explanations of the RV signal for HD 19522 and suggests that the companion must have an angular separation below a few tenths of an arcsecond. This work highlights the importance of combined RV and imaging observations for characterizing the outer regions of nearby planetary systems. © 2021 Institute of Physics Publishing. All rights reserved.
Keywords: dept.phy; peer-reviewed

Speckle observations of TESS exoplanet host stars: Understanding the binary exoplanet host star orbital period distribution - Howell, Steve B; Matson, Rachel A.; Ciardi, David R; Everett, Mark E; Livingston, John H.; Scott, Nicholas J; Horch, Elliott P; Winn, Joshua N (Astronomical Journal, 2021)
We present high-resolution speckle interferometric imaging observations of TESS exoplanet host stars using the NN-EXPLORE Exoplanet and Stellar Speckle Imager instrument at the 3.5 m WIYN telescope. Eight TESS objects of interest that were originally discovered by Kepler were previously observed using the Differential Speckle Survey Instrument. Speckle observations of 186 TESS stars were carried out, and 45 (24%) likely bound companions were detected. This is approximately the number of companions we would expect to observe given the established 46% binarity rate in exoplanet host stars. For the detected binaries, the distribution of stellar mass ratio is consistent with that of the standard Raghavan distribution and may show a decrease in high-q systems as the binary separation increases. The distribution of binary orbital periods, however, is not consistent with the standard Ragahavan model, and our observations support the premise that exoplanet-hosting stars with binary companions have, in general, wider orbital separations than field binaries. We find that exoplanet-hosting binary star systems show a distribution peaking near 100 au, higher than the 40–50 au peak that is observed for field binaries. This fact led to earlier suggestions that planet formation is suppressed in close binaries.
Keywords: dept.phy; peer-reviewed

Identifying bound stellar companions to kepler exoplanet host stars using speckle imaging - Colton, Nicole M.; Horch, Elliott P; Everett, Mark E; Howell, Steve B; Davidson, James W., Jr.; Baptista, Brian J.; Casetti-Dinescu, Dana I (Astronomical Journal, 2021)
The Kepler mission and subsequent ground-based follow-up observations have revealed a number of exoplanet host stars with nearby stellar companions. This study presents speckle observations of 57 Kepler objects of interest (KOIs) that are also double stars, each observed over a 3-8 yr period, which has allowed us to track their relative motions with high precision. Measuring the position angle and separation of the companion with respect to the primary can help determine if the pair exhibits common proper motion, indicating it is likely to be a bound binary system. We report on the motions of 34 KOIs that have close stellar companions, three of which are triple stars, for a total of 37 companions studied. Eighteen of the 34 systems are confirmed exoplanet hosts, including one triple star, while four other systems have been subsequently judged to be false positives and twelve are yet to be confirmed as planet hosts. We find that 21 are most likely to be common proper motion pairs, 4 are line-of-sight companions, and 12 are of an uncertain disposition at present. The fraction of the confirmed exoplanet host systems that are common proper motion pairs is approximately 86% in this sample. In this subsample, the planets are exclusively found with periods of less than 110 days, so that in all cases the stellar companion is found at a much larger separation from the planet host star than the planet itself. A preliminary period-radius relation for the confirmed planets in our sample suggests no obvious differences at this stage with the full sample of known exoplanets. © 2020. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; peer-reviewed

HAT-P-68b: A transiting hot jupiter around a K5 dwarf star - Lindor, Bethlee M.; Hartman, Joel D.; Bakos, Gáspár Á.; Bhatti, Waqas; Csubry, Zoltan; Penev, Kaloyan; Bieryla, Allyson; Lathman, David W; Torres, Guillermo; Buchhave, Lars A; de Val-Borro, Miguel; Howard, Andrew W; et al. (Astronomical Journal, 2021)
We report the discovery by the ground-based Hungarian-made Automated Telescope Network (HATNet) survey of the transiting exoplanet HAT-P-68b, which has a mass of 0.724 ± 0.043 MJ, and radius of 1.072 ± 0.012 RJ. The planet is in a circular P = 2.2984 day orbit around a moderately bright V = 13.937 ± 0.030 magnitude K-dwarf star of mass ${0.673}_{-0.014}^{+0.020}$ M⊙, and radius 0.6726 ± 0.0069 R⊙. The planetary nature of this system is confirmed through follow-up transit photometry obtained with the Fred L. Whipple Observatory (FLWO) 1.2 m telescope, high-precision radial velocities measured using Keck I/High Resolution Echelle Spectrometer (HIRES), FLWO 1.5 m/Tillinghast Reflector Echelle Spectrograph (TRES), and Observatoire de Haute-Provence (OHP) 1.9 m/Sophie, and high-spatial-resolution speckle imaging from WIYN 3.5 m/DSSI. HAT-P-68 is at an ecliptic latitude of +3° and outside the field of view of both the NASA Transiting Exoplanet Survey Satellite primary mission and the K2 mission. The large transit depth of 0.036 mag (r band) makes HAT-P-68b a promising target for atmospheric characterization via transmission spectroscopy.
Keywords: dept.phy; peer-reviewed